Cylindrical core-shell tween 80 micelle templated green synthesis of gold-silver hollow cubic nanostructures as efficient nanocatalysts. (15th December 2018) - Joseph, Dickson; Lee, Hoomin; Huh, Yun Suk; Han, Young-Kyu
Abstract: The non-ionic surfactant, Tween 80 (T80) a material with promising applications in the pharmaceutical, cosmetic, and food industries, has been explored here for the design of novel nanostructures (NS). We report here a direct one-pot seedless green method for the synthesis of gold-silver (AuAg) hollow cubic NS, with gold (90%) being the major component. The concentration of T80 plays an important role in determining the shape of the NS. A minimum T80 concentration of 50 mM is required for the formation of hollow cubic NS, whose sizes are controlled by increasing the T80 concentration. The unique molecular structure of T80 directs its molecules to assemble into core-shell cylindrical micelles that act as a soft-template for the growth of the NS. Study of the mechanism for the formation of the NS suggests nucleation followed by co-reduction of metal ions and its growth into hollow cubic NS over T80 micelles. The AuAg hollow cubic NS shows greater potential as efficient nanocatalysts than the non-cubic NS obtained at lower T80 concentrations. The hollowness and the cubic shape of the NS contribute towards their effective surface area that facilitates efficient catalytic activity. The AuAg NS may have biological applications due to their cell viabilities. Graphical abstract: Tween 80, a biocompatible non-ionic surfactant as a soft-template for the synthesis of novel gold-silver hollow cubic nanostructures as nanocatalysts, using a direct one-pot seedless method in aqueous medium. Highlights: A green, direct, one-pot, seedless route towards the synthesis of hollow cubic nanostructures has been successfully developed. The hollow cubic nanostructures are made up of a bimetallic gold-silver alloy, with gold as the major component. Tween 80, a non-ionic surfactant's core-shell cylindrical micellar structure guides the shape of the nanostructures. The prepared nanostructures are biocompatible and act as efficient nanocatalysts.